A Prospective Study of the Safety and Efficacy of a Microneedle Fractional Radiofrequency System for Global Facial Photoaging in Chinese Patients. Issue 7 (July 2018) - Zhang, Mengli; Fang, Jing; Wu, Qiuju; Lin, Tong
Abstract : BACKGROUND: Facial photoaging has become a major cosmetic concern, and the microneedle fractional radiofrequency system (MFRS) is a novel method for rejuvenation that combines radiofrequency and microneedles. OBJECTIVE: This study prospectively evaluated the efficacy and safety of an MFRS in the treatment of facial photoaged skin in Chinese patients. MATERIALS AND METHODS: Twenty-seven patients with moderate facial photoaging were recruited and received 3 treatments at 4-week intervals. Blinded clinical assessment was performed by 2 independent dermatologists on a 5-point global photoaging scale (GPS). Patients were also questioned on the extent of improvement of rhytides, skin tightening, and complexion with a 4-point global aesthetic improvement scale (GAIS) and satisfaction based on a 5-point scale. Adverse events and pain scores were also evaluated. RESULTS: Compared with the baseline, there was a significant improvement in facial photoaged skin after 3 treatments, and these positive outcomes were maintained up to the 6-month follow-up, according to the GPS and GAIS scores. Most patients were satisfied with the treatment and reported mild to moderate pain and adverse effects. CONCLUSION: This MFRS is effective for facial skin rejuvenation in Chinese patients. The therapy also seems safe and well tolerated.